Pendampingan Digitalisasi Aset Desa Melalui Website Smart Village di Mondoretno Kecamatan Bulu Temanggung - Robingun Suyud El Syam; Ilhan Mansyur Al Huda; Ivan Geovani; Khamid Murtadho; Muhammad Abdul Latif; Izzul Fahmi Al Kholiq; Dwi Rahmat Setiyono (Jurnal Kemitraan Masyarakat, 2025)
One of the important steps to improve transparency, effectiveness, and accountability in village governance is the digitalization of village assets. This program aims to use digital tools to improve asset management, make data access easier, and help improve decision-making processes. The focus of this study is to support the digitalization of village assets through the creation and implementation of the Smart Village website in Mondoretno Village, Bulu District, Temanggung Regency. The mentoring strategy includes four steps, namely Digital village asset inventory, Collaboration with third parties, Promoting to the community, and Capacity building through feedback. The results of the mentoring show a significant increase in data organization, ease of access, and the ability of village officials to use digital platforms. In addition, the Smart Village website functions as a center for information and administrative activities. This website helps build a more sophisticated and connected village governance system. This study found that digital technology in village asset management is not only possible, but also effective in addressing the problems faced by rural communities. The success of the program in Mondoretno Village provides a model that can be used by other villages that want to change their lives to the computer and internet era.